Preparation of Ti/SnO2-Sb/Rare Earth Electrodes Containing Different Contents of Ni Intermediate Layer for Efficient Electrochemical Decolorization of Rhodamine B. (31st May 2021) - Wai, Thet Phyo; Yin, Yilin; Zhang, Xiao; Li, Zenghe
Abstract : Water contamination by dyes discharged from many industries is an environmental issue of great matter. Electrochemical oxidation is an advanced approach for wastewater treatment. In this study, the composite electrodes of Ti/SnO2 -Sb-Ni/rare earth have been modified using rare earth elements (Re) Gd, Ce, Eu, and Er and various molar ratios of tin and nickel intermediate layer, and their electrochemical oxidation effects were scrutinized. To analyze the decolorization performance of the electrodes, Rhodamine B (RhB) dye was utilized as a target pollutant. Accelerated life testing indicated that the longer service life could be observed in Ni (3.5%)/Re and Ni (5%)/ Re electrodes compared with other modified Ni (0%, 1%, and 2%)/Re electrodes. Compared with the color removal efficiencies of the Ni (2%)/Re electrodes, the decolorization rate of 90% after treatment for 60 min and the low energy consumption of 3.621 kW h·m −3 can be achieved at the Ni (2%)/Gd electrode under the experimental condition of 100 mg·L −1 RhB. The best decolorization rate was observed at the Ni (2%)/Re electrodes among other Ni and no adding Ni-doped Re electrodes. The characterization of the electrodes was described, consisting of surface morphology, oxygen evolution potential, and a crystallographic and elemental combination of the coatings.